(untitled) (Current Problems in Rail Vehicles, 2021)
The article focuses on a comparison of running characteristics of rail freight bogies when negotiating curves of small radiuses. The conventional bogie Y25 and the bogie with radially adjustable wheelsets TVP-NG2 are compared. Emphasis was placed on effect of used rail head profile and also on rail head wear effect upon running and operational characteristics of the bogies.